Atrial Fibrillation Ablation in Heart Failure and Preserved Ejection Fraction: An Observational Study of Risk Factors for Heart Failure Hospitalization - Qi, Rundi; Liu, Hailei; Zhu, Yue; Wu, Nan; Wang, Kexin; Ding, Xiangwei; Gu, Zhoushan; Li, Mingfang; Chen, Hongwu; Ju, Weizhu; Li, Xin; Chen, Minglong (Current Cardiology Reviews, 2025)
IntroductionLong-term heart failure hospitalization (HFH) after radiofrequency catheter ablation (RFCA) in atrial fibrillation (AF) patients with heart failure and preserved ejection fraction (HFpEF) and its risk factors remain to be investigated.MethodsAF patients with HFpEF who underwent RFCA from January, 2014 to December, 2018 from three centers were retrospectively included. Patients were assigned to the training and testing cohorts, respectively. In the training cohort, logistic regression analyses were performed to discriminate those with and without HFH. A scoring system was developed accordingly and validated.ResultsA total of 417 AF patients with HFpEF receiving RFCA were enrolled. About 35 patients (8.4%) had HFH for 6 years. In the training cohort, the use of diuretics, atrial tachycardia (AT)/AF recurrence, prior HFH, and female sex were independent predictors of HFH in the multivariable analysis. A DAPF score (ranging from 0 to 9.0) was developed. The area under the receiver operating characteristic curve (AUC) of the DAPF score was 0.880 (95% CI, 0.830-0.929). A DAPF score ≥3.5 could predict HFH with a sensitivity of 81.8% and a specificity of 74.6%. The performance in the testing cohort remained robust (AUC, 0.858; 95% CI, 0.749-0.967).ConclusionHFH in patients with AF and HFpEF after RFCA is not rare. The DAPF score could predict the risk of HFH in AF patients with HFpEF after RFCA and guide our treatment strategy.
Keywords: cardiovascular outcomes